Grain boundary diffusion neodymium-iron-boron magnet base material and preparation method of grain boundary diffusion neodymium-iron-boron magnet
Through the grain boundary diffusion process of controlling element ratio and refined regulation, the conflict between coercive force and magnetic energy product of neodymium iron boron materials is solved, high residual magnetism and high coercive force are achieved, and production costs are reduced.
Patent Information
- Application Number
- CN202411251946.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When traditional sintered NdFeB materials increase coercivity, the magnetic energy accumulation decreases, and heavy rare earth resources are scarce and expensive, resulting in increased product costs and it is difficult to achieve high magnetic energy accumulation and high coercivity.
By controlling the proportion of elements and the refined regulation of the preparation process, the grain boundary diffusion process is adopted, including smelting rapid condensation, hydrogen crushing, airflow grinding, molding and pressing, vacuum sintering, acid etching and application of diffusing agents, and two stages of low-temperature heat treatment are carried out. , a high residual magnet neodymium iron boron magnet substrate is formed.
The substrate coercive force has been greatly increased and only a small amount of residual magnetism has been lost, which has reduced production and manufacturing costs and simplified the grain boundary diffusion process.
Smart Images

Figure CN119252635A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sintered NdFeB materials, and in particular to a grain boundary diffused NdFeB magnet substrate and a preparation method of the grain boundary diffused NdFeB magnet. Background Art
[0002] Sintered NdFeB permanent magnet materials, with their excellent magnetic properties, high magnetic energy product, excellent coercive force and residual magnetic retention, are widely used in many key fields such as electronic equipment, automotive industry, magnetic transmission, medical equipment and precision instruments. It is not only the core component of high-performance products such as speakers, hard disk drives, electric vehicle motors, but also promotes the green and efficient process of industrial equipment. With the continuous advancement of technology, the application prospects of sintered NdFeB will be broader, and it will continue to lead the development trend of modern industry and technology.
[0003] The maximum magnetic energy product (BH) max (the efficiency of the motor in converting electrical energy into kinetic energy) and the intrinsic coercivity Hcj (the ability to resist demagnetization under service conditions) have always been the key indicators for measuring the performance of NdFeB, and directly determine its application areas. However, there is a certain conflict between the two. The traditional production process can achieve a substantial increase in coercivity by adding a large amount (5wt.%) of heavy rare earths (terbium, dysprosium, holmium), etc., but heavy rare earths and iron are antiferromagnetically coupled, so the magnetic energy product of the prepared NdFeB is seriously reduced. In addition, heavy rare earths are scarce resources, and there are almost no heavy rare earths in rare earth mines in northern my country. The price is very expensive (terbium Tb-6100 yuan / kg, dysprosium 2100 yuan / kg). While the product cost increases, it cannot simultaneously achieve high magnetic energy product ((BH) max>52MGOe) and high coercivity (Hcj>17kOe).
[0004] On the other hand, the emerging heavy rare earth grain boundary diffusion technology has been proven to be able to improve the coercivity of magnets with a small loss of magnet remanence (related to the magnetic energy product strength). However, grain boundary diffusion is heavily dependent on the grain boundary phase of NdFeB, and a major feature of high magnetic energy product magnets is the lack of grain boundary phase, which makes it impossible to effectively carry out grain boundary diffusion. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a grain boundary diffused NdFeB magnet substrate and a method for preparing the grain boundary diffused NdFeB magnet, and provides a simple and effective grain boundary diffusion process for high remanence NdFeB.
[0006] To achieve the above objectives, the technical solution of the present invention is implemented through the following technical solutions:
[0007] A grain boundary diffused NdFeB magnet substrate, wherein the components of the grain boundary diffused NdFeB magnet substrate are as follows: 29.2%≤Nd≤29.6%, 0.96%≤B≤0.98%, Cu+Ga≤0.2%, Zr≤0.15%, Co≤1%, 0≤Ti≤0.06%, and the remainder is iron and inevitable impurities.
[0008] The method for preparing a grain boundary diffused NdFeB magnet comprises the following steps:
[0009] S1. Prepare the grain boundary diffused NdFeB magnet substrate according to claim 1:
[0010] S1-1, preparing materials according to the mass percentage of raw materials, and then mixing the raw materials for melting and rapid solidification to obtain a base alloy;
[0011] S1-2, hydrogen crushing and air flow milling of the above-mentioned base alloy to obtain alloy powder for later use;
[0012] S1-3, forming and pressing the alloy powder to obtain a green body for later use;
[0013] S1-4, vacuum sintering the green body to obtain a grain boundary diffused NdFeB magnet substrate as a base magnet;
[0014] S2, etching the base magnet in nitric acid, taking it out and drying it, quickly and evenly coating the surface of the base magnet with a diffusing agent, and then drying it to obtain a coated magnet, wherein the diffusing agent is composed of TbF3 / DyF3, a curing agent, and vinyl butyral;
[0015] S3. The coated magnet is subjected to two stages of low temperature heat treatment to obtain a grain boundary diffused NdFeB magnet.
[0016] Preferably, the specific conditions for melting and rapid solidification in step S1-1 are melting at a temperature of 1470-1490°C for 5-8 min in an argon atmosphere of 0.8-0.9 MPa, and controlling the temperature of subsequent rapid solidification pouring to 1430-1450°C, and the average thickness of the obtained rapid solidification sheet is 0.29-0.3 mm.
[0017] Preferably, the hydrogen crushing in step S1-2 is performed in an oxygen-free environment to fully absorb hydrogen, and a lubricant of 0.15% of the total mass of the base alloy is added; the speed of the air flow mill is 4000-4500r / min, and the SMD of the final alloy powder is 3.3-3.7μm.
[0018] Preferably, the molding pressing in step S1-3 is carried out by an orientation pressing method: the orientation current is controlled to be greater than 100A, the demagnetization current is 5-7A, the molding pressure is 8Mpa, the isostatic pressure is 200Mpa, and the oxygen content is controlled to be lower than 20ppm during the pressing process, and the pressing time is 5-10s.
[0019] Preferably, the specific method of vacuum sintering in step S1-4 is: after the green body is placed in the sintering furnace, argon gas is purged 2-3 times, and then the vacuum degree is less than 1×10 -3 Pa, first heated from room temperature to 350±50℃ and kept warm for 30min, then heated to 850±50℃ and kept warm for 30min, then heated to 1070-1080℃ and kept warm for 3-6h. After sintering, 0.9Mpa argon gas was introduced and the heating equipment was removed to expose the outer furnace tube and air-cooled to obtain the base magnet.
[0020] Preferably, in step S2, nitric acid with a concentration of 2%-5% is used for acid etching for 2-5 minutes, and after the acid etching, the base magnet is placed in ethanol for ultrasonic cleaning, and then the air humidity is controlled to be lower than 20% and dried at room temperature.
[0021] Preferably, in step S2, the curing agent is any one or more of methanol, ethanol, propyl acetate, and isopropanol, and the mass ratio of TbF3 / DyF3, curing agent, and vinyl butyral in the diffusant is 60-68:25-35:0.8-1.2; and the diffusant is applied by first applying it to the surface of the base magnet by brush printing in an environment with a humidity of 10%-20%, and then drying it at 80-100°C for 20-70 minutes, and after coating, the base magnet increases in weight by 1%-2% compared with the raw material.
[0022] Preferably, the specific manner of the two-stage low-temperature heat treatment in step S3 is that the first stage heat treatment temperature is 880-950°C and the time is 180-360 min, and the second stage heat treatment temperature is 500-520°C and the time is 180-240 min.
[0023] Preferably, the two low-temperature heat treatments in step S3 are performed at a vacuum degree of less than 10 -3 After the heat treatment, argon gas is filled to 0.9 MPa and then the temperature is lowered.
[0024] The present invention provides a grain boundary diffused NdFeB magnet substrate and a method for preparing the grain boundary diffused NdFeB magnet, which have the following advantages over the prior art:
[0025] The present invention can solve the problem that the missing grain boundaries of high remanent magnetism NdFeB cannot effectively diffuse by controlling the element ratio and fine regulation during the preparation process, so that the coercivity of the substrate is greatly increased and only a small amount of remanence is lost. In addition, the grain boundary diffusion process of the present invention, especially the coating process, is very simple, and the production cost will be greatly reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Schematic diagram comparing the magnetic field changes of a base magnet prepared using materials from experimental group 1 and a NdFeB diffused magnet prepared using materials from experimental group 1 in Example 1 of the present invention. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Embodiment 1:
[0029] 1. Preparation of base magnet:
[0030] 1. Melting and quick setting: After cleaning the crucible and repairing the tundish, put the raw materials in and start to evacuate; when the vacuum degree drops below 3Pa, perform two gas washings, each time filling with argon gas to 90000Pa and then evacuate, start preheating and drying; when the vacuum degree no longer increases and returns to below 3Pa, start heating and melting; melt at 1470℃ for 6min, and then cast at a temperature range of 1440-1450℃. After casting, quickly fill with 70000Pa of argon gas and turn on the cooling fan to cool, and obtain quick setting sheets;
[0031] 2. Select quick-setting tablets with a silvery white appearance and a thickness of 0.29-0.3 mm, perform hydrogen crushing and air flow milling in an oxygen-free environment, and add 0.15% lubricant (commercially available Shell Rimula R6M) of the total mass of the quick-setting tablets during hydrogen crushing; control the speed of the air flow mill to 4200 r / min, and the final particle size of the alloy powder is 3.69 μm;
[0032] 3. Carry out orientation pressing when the oxygen content is lower than 20ppm, control the orientation current to be greater than 100A, the demagnetization current to be 5-7A, the molding pressure to be 8Mpa, the isostatic pressure to be 200Mpa, and the pressing time to be 8s.
[0033] 4. Perform three vacuum cleanings, with the vacuum degree lower than 3Pa; then use a molecular pump to reduce the vacuum degree to 10 -3Pa; heated from room temperature to 350℃, with a heating rate of 8℃ / min, kept warm for half an hour, then heated to 850℃ at 6℃ / min, kept warm for half an hour, then heated to the temperature required for densification (1070-1080℃) at 5℃ / min and kept warm for 4h; after sintering, 0.9Mpa argon gas was introduced and the heating equipment was removed to expose the outer furnace tube and air-cooled to obtain the base magnet.
[0034] 2. Preparation of Grain Boundary Diffusion NdFeB Magnets (Grain Boundary Diffusion Process)
[0035] 1. Preparation of diffusant: Dissolve 65% TbF3 in a mixture of anhydrous ethanol and polyvinyl butyral (PVB) (mass ratio 6:1), stir until completely mixed to obtain a diffusant for use;
[0036] 2. Cut the sintered base magnet into a Φ10*H 3.5 (mm) cylinder with the C axis as the radial direction. After polishing, place it in 3% nitric acid for 3 minutes, and then ultrasonically clean it for later use;
[0037] 3. Apply the diffusant evenly on the surface of the magnet circle in an environment with a humidity of 10%-20%, with a coating thickness of 1.5mm, and dry it at 90℃ for 30 minutes.
[0038] 4. The magnet coated with the diffusant is subjected to two-stage heat treatment to obtain a NdFeB diffused magnet.
[0039] 3. Referring to the above preparation process, each group of base magnets was prepared according to the mass percentage of the raw materials in Table 1 below:
[0040] Table 1
[0041]
[0042]
[0043] Detection:
[0044] 1. The magnetic properties of the base magnets prepared from the materials of the experimental groups 1-5 and the control groups 1-5 and the densification temperature of the magnetic properties of the base magnets prepared from the materials of the experimental groups 1-5 were detected. The specific results are shown in Table 2 below:
[0045] Table 2
[0046]
[0047] According to Table 2 above, the Nd content in the control group 1 is 29.1%, the coercive force is reduced, and the magnetic energy product is insufficient; the Cu+Ga content in the control group 2 is 0.32%, which does not belong to high remanence, and the magnetic energy product is reduced; the Nd content in the control group 3 is 30%, and the remanence is too low; the B content in the control group 4 is 0.95%, and the coercive force is too low; the Nd content in the control group 5 is 29.8%, the Zr content is 0.2%, and the magnetic energy product does not exceed 50MGOe.
[0048] 2. The magnetic properties of the NdFeB diffusion magnets made from the material ratios of the above experimental groups 1-5, as well as the primary heat treatment and secondary heat treatment conditions, were tested. The specific results are shown in Table 3 below:
[0049] Table 3
[0050]
[0051] 3. The NdFeB diffused magnets made according to the material ratios of experimental groups 1-5 were subjected to the primary heat treatment at 960°C for 3 hours and the secondary heat treatment at 480°C for 3 hours. The magnetic properties of the NdFeB diffused magnets of each group were tested. The specific results are shown in Table 4 below:
[0052] Table 4
[0053] Group Br / kGs HkDJ (BH)max / MGOe Experimental Group 1 14.42 14.35 51.97 Experimental Group 2 14.62 12.32 52.01 Experimental Group 3 14.70 14.68 51.78 Experimental Group 4 14.68 14.44 51.14 Experimental Group 5 14.43 17.03 51.41
[0054] It can be seen from the above table that the magnetic properties of the NdFeB diffusion magnet treated with the primary heat treatment temperature at 960°C and the secondary heat treatment temperature at 480°C are significantly lower than those of the NdFeB diffusion magnet treated with the primary heat treatment temperature at 880-950°C and the secondary heat treatment temperature at 500-520°C in Table 3.
[0055] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A grain boundary diffused NdFeB magnet substrate, characterized in that: The components of the grain boundary diffused NdFeB magnet substrate are as follows in percentage by mass: 29.2%≤Nd≤29.6%, 0.96%≤B≤0.98%, Cu+Ga≤0.2%, Zr≤0.15%, Co≤1%, 0≤Ti≤0.06%, and the remainder is iron and inevitable impurities.
2. A method for preparing a grain boundary diffused NdFeB magnet, characterized in that: The preparation method comprises the following steps: S1. Prepare the grain boundary diffused NdFeB magnet substrate according to claim 1: S1-1, preparing materials according to the mass percentage of raw materials, and then mixing the raw materials for melting and rapid solidification to obtain a base alloy; S1-2, hydrogen crushing and air flow milling of the above-mentioned base alloy to obtain alloy powder for later use; S1-3, forming and pressing the alloy powder to obtain a green body for later use; S1-4, vacuum sintering the green body to obtain a grain boundary diffused NdFeB magnet substrate as a base magnet; S2, etching the base magnet in nitric acid, taking it out and drying it, quickly and evenly coating the surface of the base magnet with a diffusing agent, and then drying it to obtain a coated magnet, wherein the diffusing agent is composed of TbF3 / DyF3, a curing agent, and vinyl butyral; S3. The coated magnet is subjected to two stages of low temperature heat treatment to obtain a grain boundary diffused NdFeB magnet.
3. The preparation method according to claim 2, characterized in that: The specific conditions for melting and rapid solidification in step S1-1 are melting at a temperature of 1470-1490°C for 5-8 minutes in an argon atmosphere of 0.8-0.9Mpa, and controlling the temperature of subsequent rapid solidification pouring to 1430-1450°C, and the average thickness of the obtained rapid solidification sheet is 0.29-0.3mm.
4. The preparation method according to claim 2, characterized in that: In the step S1-2, the hydrogen crushing is performed in an oxygen-free environment to fully absorb hydrogen, and a lubricant of 0.15% of the total mass of the base alloy is added; the speed of the air flow mill is 4000-4500 r / min, and the SMD of the final alloy powder is 3.3-3.7 μm.
5. The preparation method according to claim 2, characterized in that: The molding and pressing in step S1-3 is carried out by an orientation pressing method: the orientation current is controlled to be greater than 100A, the demagnetization current is 5-7A, the molding pressure is 8Mpa, the isostatic pressure is 200Mpa, and the oxygen content is controlled to be lower than 20ppm during the pressing process, and the pressing time is 5-10s.
6. The preparation method according to claim 2, characterized in that: The specific method of vacuum sintering in step S1-4 is: after the green body is placed in the sintering furnace, argon gas is used for purging 2-3 times, and then the vacuum degree is less than 1×10 -3 Pa, first heated from room temperature to 350±50℃ and kept warm for 30min, then heated to 850±50℃ and kept warm for 30min, then heated to 1070-1080℃ and kept warm for 3-6h. After sintering, 0.9Mpa argon gas was introduced and the heating equipment was removed to expose the outer furnace tube and air-cooled to obtain the base magnet.
7. The preparation method according to claim 2, characterized in that: In step S2, nitric acid with a concentration of 2%-5% is used for acid etching for 2-5 minutes, and after the acid etching, the base magnet is placed in ethanol for ultrasonic cleaning, and then the air humidity is controlled to be lower than 20% and dried at room temperature.
8. The preparation method according to claim 2, characterized in that: In step S2, the curing agent is any one or more of methanol, ethanol, propyl acetate, and isopropanol, and the mass ratio of TbF3 / DyF3, curing agent, and vinyl butyral in the diffusing agent is 60-68:25-35:0.8-1.2; and the diffusing agent is applied by first applying it to the surface of the base magnet by brush printing in an environment with a humidity of 10%-20%, and then drying it at a temperature of 80-100°C for 20-70 minutes, and after coating, the base magnet increases in weight by 1%-2% compared with the raw material.
9. The preparation method according to claim 2, characterized in that: The specific method of the two-stage low-temperature heat treatment in step S3 is that the first stage heat treatment temperature is 880-950°C and the time is 180-360 minutes, and the second stage heat treatment temperature is 500-520°C and the time is 180-240 minutes.
10. The preparation method according to claim 9, characterized in that: In step S3, the two low-temperature heat treatments are performed at a vacuum degree of less than 10 -3 After the heat treatment, argon gas is filled to 0.9 MPa and then the temperature is lowered.
Citation Information
Patent Citations
Preparation method of yttrium-enriching permanent magnet material
CN105788794A
Method for preparing R-Fe-B sintered magnets
CN106158347A
Grain boundary diffusion neodymium iron boron magnet base material, grain boundary diffusion neodymium iron boron magnet and preparation method of grain boundary diffusion neodymium iron boron magnet
CN118248423A
Method for producing a sintered r-iron-boron magnet
US20180061540A1
Cited By
Corrosion-resistant grain boundary diffusion neodymium-iron-boron magnet and preparation method thereof
CN119694773A
